Social Psychological Conditions of Formation and Development of A Young Family - Mamatova Nazira Djurakulovna (Genius Journals, 2022)
The main factors of preparing young people for family and their psychological characteristics are described in the article, these factors were empirically researched, psychological analysis was given, conclusions and recommendations were developed based on the results.
Keywords: family; family formation factors; perceptions; relationships